Active mobility in historical districts: towards an accessible and competitive city. The case study of Pizzofalcone in Naples. - Gargiulo, Carmela; Sgambati, Sabrina (TeMA - Journal of Land Use, Mobility and Environment, 2022)
Active mobility, in the form of walking and cycling, is one of the most affordable and practical ways to promote sustainable modes of transport in urban areas, creating walkable, safe, healthy and livable environments. Given its multiple beneficial effects, the scientific community frequently considers it as a driver of urban regeneration, highlighting its role in the enhancement of accessibility and competitiveness. This study aims to deepen the role of active mobility in the redevelopment of historical districts characterized by economic and social marginality, as well as consider the resulting improvement of connectivity, attractiveness, and quality of life. To this end, we identify and classify strategies and best practices of active mobility provided by recent papers and international reports. In addition, we propose the application to a significant case study, Pizzofalcone, in the City of Naples. The area, characterized by high historical, architectural, landscape and cultural value, is not integrated with the rest of the historic city center and currently suffers economic and social marginality. The project proposal, which suggests the redevelopment of the area by redesigning pedestrian and cyclist paths, could be an interesting and economical solution to make Pizzofalcone a fundamental hub for the city and a crossing point for a multitude of people